Analysis Of Service Facilities On The Distribution Pattern Of Stunting Toddlers - Sutarto, Sutarto; Sari, Ratna Dewi Puspita; Trijayanthi, Winda; Indriyani, Reni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Stunting is a serious health issue in Indonesia, particularly affecting toddlers and their physical and cognitive growth. Nutritional, health, environmental, and socio-economic factors and health service facilities play significant roles. This study analyzes service determinants and their influence on stunting distribution patterns. The findings are expected to offer recommendations for reducing stunting prevalence through improved health service quality, optimal agricultural land use, and better food facilities. The research conducted in Pesawaran Regency, Lampung Province, uses a qualitative approach to analyze stunting distribution with health services via the QGis application. Subjects were stunted toddlers, with coordinate data collected by a survey team and additional information from parent interviews. The analysis shows stunting is evenly distributed, with high concentrations in central, northern, and southern coastal areas. Despite widespread health center access, no clear relationship exists between proximity to health centers and reduced stunting. Geographical factors, clean water availability, and food facilities impact stunting distribution. Expanding agricultural land and evenly distributing health workers are necessary to mitigate stunting